1978
DOI: 10.1007/bf01352294
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear sensitivity in anurans and reptiles measured by light scattering spectroscopy

Abstract: Summary. 1. We have used a light scattering spectroscopy technique to measure the vibration amplitude, in response to sound stimuli, of the eardrums of two species of anurans (Bufo arnericanus and Hyla cinerea) and one reptile species (Chrysemys scripta elegans).2. The amplitude of displacement as a function of frequency of the eardrums for constant sound intensity varies in a species-specific manner (Figs. 2, 5, and 7).3. The middle ear responds like a low-pass filter with the cut-off frequency differing in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 53 publications
(56 reference statements)
2
20
1
Order By: Relevance
“…The lowest threshold in air at 61 dB SPL corresponds to a tympanic disc vibration of approximately 3.6 mm s 21 (0.5 nm displacement at 500 Hz). Direct measurements of disc transfer function using light scattering spectroscopy [35] showed peak amplitudes of 15-50 nm at 500 Hz and 90 dB SPL sound pressure, so these measurements are comparable. Whole-body vibrograms had a best frequency of 100-200 Hz, lower than both sound and disc vibration audiograms.…”
Section: Discussionmentioning
confidence: 88%
“…The lowest threshold in air at 61 dB SPL corresponds to a tympanic disc vibration of approximately 3.6 mm s 21 (0.5 nm displacement at 500 Hz). Direct measurements of disc transfer function using light scattering spectroscopy [35] showed peak amplitudes of 15-50 nm at 500 Hz and 90 dB SPL sound pressure, so these measurements are comparable. Whole-body vibrograms had a best frequency of 100-200 Hz, lower than both sound and disc vibration audiograms.…”
Section: Discussionmentioning
confidence: 88%
“…The auditory range, reflected in the distribution of characteristic frequencies from about 30-700 Hz was also comparable to the range found in intact chelonia at room temperature, although Adrian et al (1938) noted that the upper frequency limit of the nerve responses was temperature-sensitive, being reduced to about 200 Hz at 10 'C. The sensitivity of the middle ear transfer in Pseudemys has been found to fall off quite steeply above 650 Hz (Moffat & Capranica, 1978) which coincides with the upper limit of the distribution of c.f.s in the auditory nerve.…”
Section: Discussionmentioning
confidence: 88%
“…If one allows for a 20 db difference in auditory nerve fibre thresholds between the two species (making the assumption that all this difference derives from the lower sensitivity of the middle ear, there is evidence to support the view that at least 10 db can be accounted for in this way: e.g. Moffat & Capranica 1978) the basilar membrane displacement in the turtle might be closer to + 0*02 nm at 40 db s.p.l. At this sound pressure, corresponding approximately to the animal's behavioural threshold (Fig.…”
Section: Nature Of the Resonancementioning
confidence: 99%
“…The mechanism behind such correlations has been investigated by diverse methodologies (Majeau-Chargois and McDanall Whitehead, 1971;Chung et al, 1978;Chung et al, 1981;Pettigrew et al, 1981;Hetherington, 1992;Boatright-Horowitz and Megela-Simmons, 1995). At another level, Moffat and Capranica (Moffat and Capranica, 1978) suggested that due to the size effect on TM resonance, the middle ear may act as a first frequency filter, as suggested by Manley for lizards (Manley, 1972). However, in most of these previous studies, the function of the middle ear was not unambiguously separated from possible participation or effects of the inner ear (including its mechanically loading the middle ear).…”
Section: Sexual Diergism Of Hearing In the Bullfrog: The Frequency Domentioning
confidence: 99%
“…The intersexual vocal communication of anurans was already described in the fourth century BC by Aristotle (Aristotle, 1984), who said that male frogs croak to attract the females, and in recent decades, this area has generated an assortment of investigations and reviews, such as Bogert (Bogert, 1960) and Schneider (Schneider, 1990). In particular, the structure and function of the anuran ear have attracted research and reviews (Capranica, 1978;Purgue and Narins, 2000;Mason, 2007). But despite recent advances (Mason and Narins, 2002a;Mason and Narins, 2002b;Mason et al, 2003;Werner, 2003), the riddle of sexually dimorphic (dually formed) and diergic [dually functioning (Rhodes and Rubin, 1999)] anuran ears has not yet been solved.…”
Section: Introductionmentioning
confidence: 99%